(untitled) (Scientific journal of the Fergana State University, 2023)
This article is about the analysis of scientific literature on terminology and terminology issues, which is currently one of the topics in the focus of world linguistics. It is in this period that one of the most difficult tasks is to find the "terminology" that has acquired a wider meaning and is studied in depth in the science of modern linguistics.